Conceptual Conflicts in Metaphors and Pragmatic Strategies for Their Translation - Rizzato, Ilaria (Frontiers in Psychology, 2021)
This article seeks to provide a theoretical exploration of Prandi’s model of conceptual conflicts in metaphors (2017) and to highlight the advantages such model presents in its applications to translation and the text analysis preceding and preparing translation. Such advantages are mainly identified in the model aptness to meet the pragmatic requirements of translation, seen as a practice-based, goal-oriented and context-driven activity. These advantages also distinctly emerge from a comparison with the main tenets of the cognitive tradition. The theoretical basis for an understanding of conceptual conflict and its applications to translation are illustrated through the analysis of three brief excerpts from literary texts in English and their Italian translation.